CRISPR'd babies: human germline genome editing in the 'He Jiankui affair'*. Issue 1 (13th August 2019) - Greely, Henry T
Abstract: The world was shocked in Nov. 25, 2018 by the revelation that He Jiankui had used clustered regularly interspaced short palindromic repeats ('CRISPR') to edit embryos—two of which had, sometime in October, become living babies. This article is an effort to provide some deep context for the He Jiankui affair and to begin analyzing it. It focuses on He's experiment, without delving into the broader ethical issues around 'human germline genome editing' in the abstract. It begins by carefully defining 'human germline genome editing'. It then describes the little we know about the experiment before providing background on CRISPR, the pre-He ethical and legal status of human germline genome editing, and on He himself. The fourth, and longest, section provides a detailed narrative of the revelation of the He experiment and its fallout. The fifth section critiques the experiment, which I believe merits unequivocal condemnation on several grounds. The last section suggests some important immediate reactions, by 'Science' and by China.